2015
DOI: 10.11124/jbisrir-2015-1898
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to promote coping and resilience in oncology and palliative care nurses caring for adult patients with malignancy: a comprehensive systematic review

Abstract: There is a need for large, well designed, multisite, experimental studies to evaluate the effectiveness of interventions that promote coping and resilience in adult palliative care or oncology nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 28 publications
1
48
0
6
Order By: Relevance
“…Alexander et al [54] reported in their pilot randomized trial that, in the experimental group, after an eight-week yoga intervention, self-care strategies significantly improved and emotional exhaustion and depersonalization decreased. In their systematic review, Gillan et al [55] outlined three principal strategies to promote nurses psychological well-being at work: foster connections within the team, develop behaviors that assist in controlling or limiting the intensity of stress by training and courses, and provide the opportunity to process emotion and create learning from experiences. In a Korean study [56], the author reported the positive effect of group rational emotive behavior therapy on the nurse job stress and burnout; this strategy also improved job satisfaction and organizational commitment and reduced the turnover intention.…”
Section: Implications For Practicementioning
confidence: 99%
“…Alexander et al [54] reported in their pilot randomized trial that, in the experimental group, after an eight-week yoga intervention, self-care strategies significantly improved and emotional exhaustion and depersonalization decreased. In their systematic review, Gillan et al [55] outlined three principal strategies to promote nurses psychological well-being at work: foster connections within the team, develop behaviors that assist in controlling or limiting the intensity of stress by training and courses, and provide the opportunity to process emotion and create learning from experiences. In a Korean study [56], the author reported the positive effect of group rational emotive behavior therapy on the nurse job stress and burnout; this strategy also improved job satisfaction and organizational commitment and reduced the turnover intention.…”
Section: Implications For Practicementioning
confidence: 99%
“…To exemplify the use of the methodology of Systematic Review of Mixed Methods in nursing, the article Strategies to promote coping and resilience in oncology and palliative care nurses caring for adult patients with malignancy: a comprehensive systematic review. 16 This review aimed to identify individual search and organizational strategies for coping and resilience in oncology and palliative care of nurse caregivers of adult patients with malignant disease. The search strategy was based on 12…”
Section: /12mentioning
confidence: 99%
“…The risk factors for burnout include: young age, very low or high professional level, female sex, psychological characteristics (low stress stability, lack of communication skills, anxiety, aggressiveness, sensitivity, domination of passive coping strategies, organizational components in the form of signi icant workload, inability to make decisions, intrateam con licts, lack of social support) [2], [3], [4], [5], [6]. As the protective factors can be considered mental endurance, high communicative competence, skills of effective counteraction to stress, adequate level of autonomy in the organization of working time and production tasks, support for colleagues and leadership [7], [8], [9], [10]. The severity and range of burnout symptoms depend on the interaction between the speci ics of professional activity and personal characteristics of the worker.…”
Section: Introductionmentioning
confidence: 99%
“…Changes caused by burnout have unfavorable consequences for the health and professional activities, which require the maintenance and provision of physicians with the necessary knowledge and skills to counteract professional stress and maintain personnel's health [8], [9], [11].…”
Section: Introductionmentioning
confidence: 99%